The Bandar-log : a Labor story of the 1950s - Reid, Alan (Alan Douglas), 1914-1987; Fitzgerald, Ross, 1944-; Holt, Stephen, 1949- (Ballarat, VIC : Connor Court Publishing, 2015)
The Bandar-Log: A Labor Story of the 1950s is a fictionalised recreation of the great Labor split of the 1950s. This schism in Labor's ranks began in October 1954 when its erratic federal party leader Dr H.V. ("Doc") Evatt denounced the perceived influence wielded over the party by the anti-communist Catholic activist B.A. ("Bob") Santamaria. The resulting donnybrook involved personality clashes as well as ideological conflict. The messy saga featured a diverse array of participants including Catholic churchmen, trade union bosses, state premiers, state and federal Labor politicians and assorted commentators and journalists..
Keywords: Australian Labor Party -- Fiction; Democratic Labor Party (Australia) -- Fiction; Politicians -- Australia -- Fiction; Australia -- Politics and government -- 1945- -- Fiction; Australian; Australian fiction; Political fiction